Technology Entrepreneurship Project (ENT 600) : Nike / Muhammad Qasri Hakim Khairul Anwar - Khairul Anwar, Muhammad Qasri Hakim (2021)
Nike is a brand and worldwide company which produce a lot of products which are shoes, apparel and equipment. In this company analysis, it focuses on one product of Nike air max which is Nike Air Vapormax Flyknit 2 to be investigate, identified and analysed along with their current problems and come out with solution. The first problem regarding their product is upper mesh and tongue unit is less durable and easily tear. As we know, Nike produced sport shoe that can be use for performing any exercise. The shoe should be durable and not easily tear to avoid any risk of injury. Without this feature, it will bring disadvantages to consumer where if the upper unit tear, it exposes the foot to any existence danger. As for the next problem air cushioning deflated after using several times. Air cushioning helps consumer to absorb impact every step. This problem could risk consumer’s leg as air cushioning is function to comfort and support consumer by absorbing impact. Lastly, another issue identified in this case study is air pods technology is deflated after using several times. Air pods technology help to support lightweight and provide bouncy effect to the customer. However, this weakness may not support the function of the shoe while it harms the consumer because of the loss of stability of the shoe. Apart from that, there are few solutions and innovation to overcome the problems. After analysed the problem, the type of weave should be considered on the upper and tongue unit of the shoe. Woven cloth is the best fabric which is durable and twill leave are believed to provide more durability compared the plain weave of Nike Air Vapormax Flyknit 2. This is due to the higher tearing strength of twill weave. Next solution is air cushioning of Nike Air Vapormax Flyknit 2 should be replaced by air cushioning of Nike React Infinity Run Flyknit. Study showed air cushioning of Nike React Infinity Run Flyknit has best air cushion among running shoe. The last solution is to increase the thickness layer of rubber on outer sole. By this solution, it will help to protect air pods technology and increase durability of the shoe. All of these solutions are need to be considered in order to improve the Nike Air Vapormax Flyknit 2. Besides, with this solution, it will increase the quality and performance of the product, at the same time satisfy customer which leads to business growth, developments and more achievements ahead.